Carbonyl Stress and Microinflammation-Related Molecules as Potential Biomarkers in Schizophrenia - Ohnuma, Tohru; Nishimon, Shohei; Takeda, Mayu; Sannohe, Takahiro; Katsuta, Narimasa; Arai, Heii (Frontiers in Psychiatry, 2018)
This literature review primarily aims to summarize our research, comprising both cross-sectional and longitudinal studies, and discuss the possibility of using microinflammation-related biomarkers as peripheral biomarkers in the diagnosis and monitoring of patients with schizophrenia. To date, several studies have been conducted on peripheral biomarkers to recognize the potential markers for the diagnosis of schizophrenia and to determine the state and effects of therapy in patients with schizophrenia. Research has established a correlation between carbonyl stress, an environmental factor, and the pathophysiology of neuropsychiatric diseases, including schizophrenia. In addition, studies on biomarkers related to these stresses have achieved results that are either replicable or exhibit consistent increases or decreases in patients with schizophrenia. For instance, pentosidine, an advanced glycation end product (AGE), is considerably elevated in patients with schizophrenia; however, low levels of vitamin B6 (a detoxifier of reactive carbonyl compounds) have also been reported in some patients with schizophrenia. Another study on peripheral markers of carbonyl stress in patients with schizophrenia revealed a correlation of higher levels of glyceraldehyde-derived AGEs with higher neurotoxicity and lower levels of soluble receptors capable of diminishing the effects of AGEs. Furthermore, studies on evoked microinflammation-related biomarkers (e.g., soluble tumor necrosis factor receptor 1) have reported relatively consistent results, suggesting the involvement of microinflammation in the pathophysiology of schizophrenia. We believe that our cross-sectional and longitudinal studies as well as various previous inflammation marker studies that could be interpreted from several perspectives, such as mild localized encephalitis and microvascular disturbance, highlighted the importance of early intervention as prevention and distinguished the possible exclusion of inflammations in schizophrenia.